Could problem lists summarize comprehensive geriatric assessments? A nationwide cross‐sectional survey on geriatricians' attitudes towards problem lists. Issue 2 (16th December 2018) - Tomita, Naoki; Kojima, Taro; Ishiki, Aiko; Ueda, Juri; Numasaki, Muneo; Okinaga, Shoji; Akishita, Masahiro; Arai, Hiroyuki
Abstract : Aim: The use of problem lists is encouraged to overcome the inconsistency in reporting comprehensive geriatric assessment results. The present study aimed to identify the latent variables influencing the use of geriatrician problem lists. Methods: Surveys were sent to all geriatricians registered with the Japan Geriatrics Society ( n = 1439) as of November 2015, and responses ( n = 204) were analyzed with univariate and exploratory factor analyses. To account for active, inactive and tentative items, the survey addressed "disease, " "symptom" and "condition" separately. Results: Most geriatricians (34.8%) composed problem lists for interdisciplinary information sharing. Nearly half of the respondents (46.6%) created problem lists for every patient. Information omissions were mainly due to the exclusion of information from other specialties (26% for omitted diseases and 12.3% for omitted symptoms), lack of time (25.5% for omitted diseases, 22.1% for omitted symptoms and 26.5% for omitted conditions), and lack of standardization of terminologies regarding observed diseases, symptoms and conditions (12.3% for omitted diseases, 19.6% for omitted symptoms and 16.7% for omitted conditions). An exploratory factor analysis, based on 20 predefined symptoms and conditions that are frequently omitted from problem lists, showed that considering the symptom "geriatric syndromes" and the condition "assistance needs in medication management" are crucial for improving problem list comprehensiveness. Conclusions: Geriatricians commonly use problem lists; however, there is considerable variation regarding the problems listed and their relationships. The listings of "geriatric syndrome" and "assistance needs in medication management" are crucial for improving problem list comprehensiveness.Geriatr Gerontol Int 2019; 19: 159–164 .